2007
DOI: 10.1177/10570837070170010108
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Research: Tales from the Field

Abstract: In 1990, the concept of teacher research was new to me. I was intrigued, as I listened to teachers present their research on a cold February Saturday at the University of Pennsylvania's Ethnography and Education Forum. School-based teachers had joined the forum to present their research-research that honored their "insider" knowledge of the classroom. Teachers read from journals they had kept throughout the year and talked about ways they had studied their students' learning. They spoke of the importance of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 7 publications
(1 reference statement)
0
22
0
Order By: Relevance
“…Previous literature within the field of music education encourages the use of teacher research in addressing contemporary and relevant issues within the profession (Conway and Borst 2001;Conway and Jeffers 2004;Leglar and Collay 2002;Regelski 1994;Robbins, Burbank, and Dunkle 2007). In addition to helping address issues that are important to practicing music teachers, teacher research can become a meaningful form of professional development.…”
Section: Implications For Professional Developmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous literature within the field of music education encourages the use of teacher research in addressing contemporary and relevant issues within the profession (Conway and Borst 2001;Conway and Jeffers 2004;Leglar and Collay 2002;Regelski 1994;Robbins, Burbank, and Dunkle 2007). In addition to helping address issues that are important to practicing music teachers, teacher research can become a meaningful form of professional development.…”
Section: Implications For Professional Developmentmentioning
confidence: 95%
“…Action research can be seen as a way for teachers to answer questions that puzzle them (Conway and Jeffers 2004;Robbins 2007). Cochran-Smith and Lytle (1999) describe this process as practical inquiry, emphasizing its utility as a way to generate or enhance practical knowledge.…”
Section: Practical Inquirymentioning
confidence: 98%
“…Robbins (2007) describes the professional development effect of teacher research for two experienced music teachers. Nieto (2003) suggests, All good teachers, whether they consciously carry out research or not, are researchers in the broadest sense of the word.…”
Section: Potential Of Teacher Research and Teacher Inquiry As Music Tmentioning
confidence: 99%
“…Keywords: teacher research; professional development; music education; practitioner inquiry Music education scholars have suggested that teacher research can be a valuable professional development for music teachers (Hartwig 2003;Robbins, Burbank, and Dunkle 2007;Wanzel 2009;Wanzel and Gordon 2007;West 2011). Teacher researchers seek answers to questions or situations they find puzzling in their classrooms, and this inquiry process is used to alter or transform classroom teaching (Cochran-Smith and Lytle 1999;Robbins in press).…”
mentioning
confidence: 98%